Molecular docking and ADMET studies of Allium cepa, Azadirachta indica and Xylopia aethiopica isolates as potential anti-viral drugs for Covid-19 - Adegbola, Peter Ifeoluwa (Virusdisease, 2021)
Plants are repository of important constituents with proven efficacy against many human diseases including viral diseases. The antiviral activity of many plants including Azadirachta indica, Xylopia aethiopica and Allium cepa has been reported. The novel coronavirus disease is no exception among viral diseases in which plant compounds could serve as potent antagonist. Therefore, our study investigated the inhibitory potentials of Azadirachta indica and Xylopia aethiopica isolates against SARS-CoV-2 viral accessory proteins and the host serine protease. The protein data (SARS-CoV-2 Papain like protease (PLpro) (PDB: 6wx4), Chymotrypsin-like main protease (3CLpro) (PDB:6YB7), SARS-CoV nsp 12 (PDB: 6nus), Host cell protease (TMPRSS1) (PDB:5ce1) were obtained from the protein data bank (PDB), while the SDS format of each Ligands were obtained from Pubchem database. Molecular docking analysis was performed with Auto Dock Vina 1.5.6 and visualization of the interaction between the ligands and protein was done with discovery studio 2019. The ADMET prediction of pharmacokinetics and toxicity properties of the ligands was obtained using vNN Web Server. Our result showed that all the plant isolates demonstrated negative Gibb’s free energy, indicating good binding affinity for both the viral and host protein. Overall, twenty-three of the forty-seven isolates showed good binding affinity comparable with dexamethasone that was used as reference drug. Although many of the compounds have good binding affinity for the viral and host proteins, based on the ADMET prediction, only Azadironic acid, Nimbionone, Nimbionol and Nimocinol all from A. indica could serve as potential drug candidate with good pharmacokinetics and toxicity profile. This study provides an insight into potential inhibitors and novel drug candidates for SARS-CoV-2. Further studies will look forward into the wet laboratory validation of Azadironic acid, Nimbionone, Nimbionol and Nimocinol against corona virus disease. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13337-021-00682-7.